MENINGKATKAN CAPAIAN LITERASI SISWA SD KELAS RENDAH DENGAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TaRL) - Shafira Ulil Ashri; Rima Rahmaniah; Syafruddin Muhdar; Haifaturrahmah Haifaturrahmah; Fauzan Fauzan; Siti Sanisah (Universitas Hamzanwadi, 2025)
Literacy achievement in low-grade students (I, II, and III) is still not optimal, students have not fully completed literacy achievement according to the standards of each class. This study aims to determine the improvement of literacy achievement of low-grade elementary school students by using the Teaching at the Right Level (TaRL) learning approach. The research was conducted using the Classroom Action Research (PTK) method in three cycles. Each cycle consisted of stages of planning, implementation, observation, and reflection. The research data were obtained from observation results, learning outcome tests, and documentation of 97 students. The results showed significant developments in the aspects of teacher activity in teaching from 64.23 to 91.00, student literacy skills in Class I increased from 50.16 to 88.88, Class II increased from 58.76 to 88.50, and Class III increased from 60.08 to 89.15, as well as student responses to the use of the TaRL approach in learning. It can be concluded that the use of the Teaching at the Right Level (TaRL) approach is effective in improving the literacy skills of low-grade elementary school students. It is recommended for educators to continue to innovate continuously in implementing the TaRL approach. This breakthrough can be a means to develop educators' creativity in improving their professionalism, which ultimately contributes to improving students' literacy skills.